Pensions today - economic, managerial, and social issues - Chybalski, Filip (red.); Marcinkiewicz, Edyta (red.) (Wydawnictwo Politechniki Łódzkiej, 2021)
The monograph includes 23 chapters addressing the problems of contemporary pensions from both a general and a national view, studied from a theoretical or empirical perspective. The book is structured as follows. First, the managerial, administrative and business aspects of retirement and pension wealth are discussed. The next five sections are devoted to very important and current problems of family and gender issues in the context of old-age social security. The subsequent six chapters refer to other social and economic aspects of pensions with some references to social security reforms. In the next three sections, some financial and actuarial issues are discussed and investigated. Finally, in the last five chapters, the authors address selected problems of pension reform with special attention paid to their policy and legal aspects. In these 23 chapters, issues concerning various countries are presented. In some chapters, a single-country empirical approach is employed (with reference to Poland, Spain, Turkey, Slovakia, Latvia, or Czechia, for example), whereas some other sections present multinational studies.
The book is double-blind peer reviewed.
Wydawnictwo PŁ nie ponosi odpowiedzialności za treść i opracowanie redakcyjne niniejszej publikacji.
Lodz University of Technology Press does not take responsibility for the content and editing of this publication.
Cover design: Gajderowicz, Aleksandra
Keywords: pensions; pension systems; retirement; retirement security; social housing for seniors; family businesses; social security institutions; gender pensions gap; pay-as-you-go pension scheme (PAYG); household budget; pension systems in post-Soviet countries; individual retirement accounts (IKE); Employee Capital Plans (ECP); employee pension scheme (PPE); employee capital plan (PPK)